The Saiva Dravida Nation: Maraimalai Adigal and the Transformation of the Nation-Religion-Language Framework - Kaushik, Arvind Swaminath (Univerzita Pardubice, 2022)
This work focuses on Tamil nationalism, specifically on its intellectual roots. It examines how the nation-religion-language paradigm underwent a conceptual distortion when it migrated from the British cultural setting to Tamil Nadu, and what this tells us about the native cultural framework. Although the Dravidian movement has been studied extensively, there has been minimal research into its early intellectual beginnings. Most researchers studying the Dravidian movement focused on the birth of Justice Party and the vision of its important leader, Tamil nationalist and separatist E. V. Ramaswami Naicker (known as ?Periyar?). While this iconoclast and atheist envisioned a Tamil nation free of religion and caste, it was a group of Saiva Vellala intellectuals, and among them especially Maraimalai Adigal (1876-1950), who sowed the seeds for a Dravidian nationalist movement. Unlike Periyar, Maraimalai Adigal was a traditionalist and a staunch follower of the Saiva Siddhanta tradition. Adigal?s thought linked nation, religion, and language in a way which calls for analysis of the very specific situation which led this Indian thinker to conceptualize Tamil people as a nation. Apparently, he reacted to the British ideas about what made Dravidians (and more specifically, Tamils) into a nation, but much more should be explained about this reaction. There are several problems with the descriptions offered by researchers concerning Adigal?s vision of ?Shaivite monotheism? being the original Tamil religion, and how does this vision relate to the building of Tamil nation. A careful reading of Adigal?s writings leads the author of this thesis to a reconsideration of the idea that this Tamil scholar simply accepted the British concept of nation and applied it to his people. Adigal?s points about purifying Tamil language seem to be of a different nature than the British focus on language as the constituent of a nation, and also his claims about Vellalas (his own jati) being the original Tamil nation need better explanation than those offered so far.
Šivaisticko-drávidský národ: Mezikulturní proměna paradigmatu vymezujícího národ náboženstvím a jazykem
Keywords: Tamilnádu; nacionalismus; národ; náboženství; jazyk; šaivasiddhánta; křesťanské myšlení; religionistika; komparativní studium kultur; Tamil Nadu; nationalism; nation; religion; language; Saiva Siddhanta; Christian thought; religious studies; comparative study of cultures